Polyester-based sealing film

CN122935486APending Publication Date: 2026-10-16TOYOBO CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202580018737.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-08
Filing Date
2025-02-19
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]但是,前述方法中,为了具有适度的层间剥离性,密封层和支撑层必须为不同的树脂组成(例如,在密封层为聚酯的情况下,支撑层必须为聚乙烯、聚丙烯等烯烃系统)

Benefits of technology

[0038]Although the polyester-based sealing film of the present invention is made of a single material, it can achieve moderate heat-sealing strength over a wide temperature range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

To solve the problems in the prior art, a polyester sealing film is provided, which can obtain moderate heat seal strength in a wide temperature range although it is a single material. The polyester sealing film has a sealing layer showing heat sealability, and a heat-resistant layer laminated on the sealing layer, wherein the surface of the sealing layer on the side not having the heat-resistant layer has a crystallinity of 0.90 or less based on ATR method, the crystallization temperature of the sealing layer determined by DSC is 93-118°C, and the heat seal strength at heat seal temperatures of 130°C, 150°C and 180°C is all 6-20 N / 15 mm when an A-PET sheet is overlapped with the sealing layer and heat sealed at a load of 0.2 MPa for 1 second.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a polyester-based sealing film, which, although made of a single material, can achieve moderate heat-sealing strength over a wide temperature range and has high transparency. Background Technology

[0002] Plastic containers are widely used in food packaging and other products. To date, interlocking caps made from plastics such as A-PET have been used as lid materials for these containers. Here, A-PET refers to amorphous PET (amorphous polyethylene terephthalate) in an amorphous state, containing 50% or more polyethylene terephthalate units, and is typically non-oriented and non-crystalline. However, in order to achieve universality of lid materials, waste reduction, and extended shelf life, the development of thin-film lids for plastic containers is underway. The films used for these lids require easy peeling by hand after heat sealing and sufficient sealing strength to prevent leakage of contents after heat sealing.

[0003] Furthermore, if a wide heat-sealing temperature range exhibits the aforementioned ease of peeling and sufficient sealing strength, it can be heat-sealed under various conditions and with appropriate machinery, thus becoming a highly versatile sealing film. One method for obtaining such a sealing film is to laminate a sealing layer and a support layer, and then peel the sealing layer from the support layer apart (see, for example, Patent Documents 1 and 2).

[0004] However, in the aforementioned methods, to achieve adequate interlayer peelability, the sealing layer and the support layer must be composed of different resins (for example, if the sealing layer is polyester, the support layer must be an olefin system such as polyethylene or polypropylene). Therefore, although the aforementioned interlayer peel-based sealing film has high functionality, the recycling of the film, which is not made of a single material (unifying the individual layers of a multi-layered packaging film into layers based on a single resin material), makes the recycling of the film, which has been required recently, difficult.

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent Document 1: Japanese Patent Application Publication No. 2001-328221

[0008] Patent Document 2: Japanese Patent Application Publication No. 2019-171792 Summary of the Invention

[0009] The problem the invention aims to solve

[0010] The purpose of this invention is to solve the problems in the prior art mentioned above, and to provide a polyester-based sealing film that, although made of a single material, can achieve moderate heat-sealing strength over a wide temperature range.

[0011] Solution for solving the problem

[0012] The polyester-based sealing film of the present invention, which is able to solve the above-mentioned problems, comprises the following structure.

[0013] That is, it includes the following components of the present invention.

[0014] [1] A polyester-based sealing film comprising: a sealing layer exhibiting heat-sealing properties, and a heat-resistant layer laminated on the aforementioned sealing layer, wherein,

[0015] The crystallinity of the surface of the aforementioned sealing layer on the side without the aforementioned heat-resistant layer, based on the ATR method, is below 0.90.

[0016] The crystallization temperature of the aforementioned sealing layer, as determined by DSC, is 93~118℃.

[0017] When the A-PET sheet is overlapped with the sealing layer and heat-sealed for 1 second under a load of 0.2MPa, the heat-sealing strength at heat-sealing temperatures of 130℃, 150℃, and 180℃ is 6~20N / 15mm.

[0018] [2] The polyester sealing film according to [1] has a haze of less than 10.0%.

[0019] [3] The polyester sealing film according to [1] or [2], wherein the thermal shrinkage rate at 150°C in both the length and width directions is 0.01 to 4.0%.

[0020] [4] The polyester sealing film according to any one of [1] to [3] further comprises particles,

[0021] The average particle size of the aforementioned particles is 0.01~6μm.

[0022] The content of the aforementioned particles in the polyester sealing film is 0.01~25% by mass.

[0023] [5] The polyester sealing film according to any one of [1] to [4], wherein the mass ratio of the particles contained in the aforementioned sealing layer to the particles contained in the aforementioned heat-resistant layer (sealing layer: heat-resistant layer) is 0:100 to 45:55.

[0024] [6] The polyester sealing film according to any one of [1] to [5], wherein the contact angle of the surface of the aforementioned sealing layer with respect to water is 21.0° or less.

[0025] [7] The polyester sealing film according to any one of [1] to [6], wherein the thickness of the aforementioned heat-resistant layer is 50 μm or less.

[0026] [8] The polyester sealing film according to any one of [1] to [7], wherein, in the aforementioned sealing layer, the content of polyester in 100% by mass of the resin constituting the aforementioned sealing layer is 50 to 100% by mass.

[0027] [9] The polyester sealing film according to [8], wherein the aforementioned polyester is homopolymer polyester and / or copolymer polyester.

[0028]

[10] A polyester-based sealing film according to any one of [1] to [9], wherein the sealing layer comprises a copolyester, and as a copolymer component of the copolyester, it comprises diethylene glycol.

[0029]

[11] According to the polyester sealing film of

[10] , when the diol content of the copolyester contained in the aforementioned sealing layer is set to 100 mol%, the diethylene glycol content ratio is 11.0 to 19.0 mol.

[0030]

[12] The polyester sealing film according to any one of [1] to

[11] , wherein, in the aforementioned heat-resistant layer, the content of polyester in 100% by mass of the resin constituting the aforementioned heat-resistant layer is 50 to 100% by mass.

[0031]

[13] The polyester sealing film according to

[12] , wherein the aforementioned polyester is homopolymer polyester and / or copolymer polyester.

[0032]

[14] According to the polyester sealing film of

[12] or

[13] , when the diol content of the polyester contained in the aforementioned heat-resistant layer is set to 100 mol%, the ethylene glycol content ratio is 70 to 100 mol.

[0033]

[15] The polyester sealing film according to any one of [1] to

[14] further comprises a surfactant.

[0034]

[16] According to the polyester sealing film of

[15] , the ratio of the concentration of the surfactant contained in the aforementioned heat-resistant layer to the concentration of the surfactant contained in the aforementioned sealing layer (heat-resistant layer: sealing layer) is 0:100 to 45:55.

[0035]

[17] A cover material comprising any one of [1] to

[16] a polyester sealing film.

[0036]

[18] A packaging material comprising any one of the polyester sealing films described in [1] to

[16] .

[0037] The effects of the invention

[0038] Although the polyester-based sealing film of the present invention is made of a single material, it can achieve moderate heat-sealing strength over a wide temperature range. Detailed Implementation

[0039] (Polyester-based sealing film)

[0040] The polyester-based sealing film of this invention is a polyester-based sealing film having a heat-sealing sealing layer and a heat-resistant layer laminated on the aforementioned sealing layer. The aforementioned sealing layer is preferably a heat-sealing layer, more preferably a layer that exhibits a heat-sealing strength of 3 N / 15 mm or more at any heat-sealing temperature of 130°C, 150°C, or 180°C when an A-PET sheet is overlapped with the sealing layer and heat-sealed for 1 second under a load of 0.2 MPa. On the other hand, the aforementioned heat-resistant layer is a layer without heat-sealing properties, more preferably a layer whose heat-sealing strength at heat-sealing temperatures of 130°C, 150°C, or 180°C is less than 3 N / 15 mm when an A-PET sheet is overlapped with the sealing layer and heat-sealed for 1 second under a load of 0.2 MPa. When the polyester-based sealing film is used as a cover material, the cover material is used as a material for sealing the opening of a container, and the sealing layer becomes the adhesive part to the container. The aforementioned heat-resistant layer can also be made into a laminated structure of two or more layers with different compositions.

[0041] (The technical meaning and significance of the physical properties described in this invention)

[0042] The crystallinity of the sealing layer surface (the side of the sealing layer without the heat-resistant layer) of the polyester-based sealing film of the present invention, based on the ATR method, is 0.90 or less. By controlling the crystallinity of the sealing layer surface based on the ATR method within the aforementioned range, a practical sealing strength can be obtained as a sealing film.

[0043] The upper limit of the crystallinity of the sealing layer surface based on the ATR method is more preferably 0.86, further preferably 0.82, and particularly preferably 0.78. By making the crystallinity of the sealing layer surface based on the ATR method 0.90 or less, sufficient sealing strength can be obtained even at low heat-sealing temperatures, which is therefore preferable. On the other hand, the lower limit of the crystallinity of the sealing layer surface based on the ATR method is not specifically set; if it is 0.10 or more, the film is less likely to break when the heat-sealed film is peeled off, which is therefore preferable, further preferably 0.20 or more, and particularly preferably 0.30 or more (i.e., preferably 0.10~0.90, 0.20~0.86, 0.30~0.82, or 0.30~0.78).

[0044] The crystallization temperature of the polyester sealing film in this invention, measured by DSC (Differential Scanning Calorimetry), is 93-118°C, with the upper limit more preferably 116°C, further preferably 114°C, and particularly preferably 112°C. This crystallization temperature is determined using a differential scanning calorimetry device (McScience Ltd., DSC3100S) at a heating rate of 10°C / min. The lower limit of the crystallization temperature is more preferably 95°C, further preferably 97°C, and particularly preferably 99°C (i.e., preferably 93-118°C, 95-116°C, 97-114°C, or 99-112°C). By keeping the crystallization temperature of the sealing layer below 118°C, crystallization of the sealing layer can be promoted during heat sealing at high temperatures, and the sealing strength will not increase excessively. Therefore, a wider temperature range for obtaining a suitable sealing strength is obtained, which is preferred. In addition, by keeping the crystallization temperature of the sealing layer above 93°C, crystallization is not promoted at lower heat sealing temperatures, and sufficient sealing strength can be obtained, which is also preferred.

[0045] Furthermore, in this invention, when the A-PET sheet is overlapped with the sealing layer and heat-sealed for 1 second under a load of 0.2 MPa, the sealing strength at 130°C, 150°C, and 180°C is 6~20 N / 15 mm. The upper limit of the sealing strength is more preferably 19 N / 15 mm, further preferably 18 N / 15 mm, and particularly preferably 17 N / 15 mm. The lower limit of the sealing strength is more preferably 7 N / 15 mm, further preferably 8 N / 15 mm, and particularly preferably 9 N / 15 mm (i.e., preferably 6~20 N / 15 mm, 7~19 N / 15 mm, 8~18 N / 15 mm, or 9~17 N / 15 mm). If the sealing strength is 20 N / 15 mm or less, easy opening is achieved, which is therefore preferred. Furthermore, if the sealing strength is 6 N / 15 mm or more, sufficient sealing strength is achieved, and after heat-sealing the film in an A-PET container filled with food, leakage of the contents is less likely, which is also preferred.

[0046] In the polyester-based sealing film of the present invention, the haze is preferably 10.0% or less. The upper limit of the haze is more preferably 8.0%, further preferably 6.0%, and particularly preferably 4.0%. By keeping the haze at 10.0% or less, the contents are clearly visible when the film is used as a packaging material or cover, which is therefore preferable. The closer the haze is to 0%, the more preferable it is; preferably, it can be 0.1% or more, and preferably 0.3% or more (i.e., preferably 0%~10.0%, 0.1%~8.0%, 0.1%~6.0%, or 0.3%~4.0%).

[0047] In the polyester-based sealing film of the present invention, the heat shrinkage rate in both the length and width directions at 150°C is preferably 0.01 to 4.0%. The lower limit of the heat shrinkage rate at 150°C is more preferably 0.1%, and even more preferably 0.4%. On the other hand, the upper limit of the heat shrinkage rate at 150°C is preferably 3.0%, more preferably 2.6%, even more preferably 2.2%, and particularly preferably 1.8% (i.e., preferably 0.01 to 4.0%, 0.01 to 3.0%, 0.1 to 2.6%, 0.1 to 2.2%, or 0.4 to 1.8%). Even when manufacturing films with a heat shrinkage rate of less than 0.01% in both the length and width directions at 150°C, no significant difference in practical effect is observed, and productivity is very low; therefore, it is not necessary to make the heat shrinkage rate at 150°C less than 0.01%. In particular, when the heat shrinkage rate at 150°C is 3.0% or less, the shrinkage of the film during heat sealing is reduced, and the A-PET container will not deform; therefore, this is preferred. The heat shrinkage rate can be appropriately adjusted by changing the amorphous components (e.g., the amount of diethylene glycol) contained in the heat-resistant layer.

[0048] In the polyester-based sealing film of the present invention, the contact angle of the sealing layer surface with water is preferably 21.0° or less. The upper limit of the contact angle is more preferably 19.0°, further preferably 17.0°, and particularly preferably 15.0°. By making the contact angle 21.0° or less, when the film is used as a packaging material or cover, the film is less prone to fogging, and the contents are clearly visible, which is therefore preferred. The lower limit of the contact angle is more preferably 5.0°, further preferably 7.0°, and particularly preferably 9.0° (i.e., preferably 5.0~21.0°, 7.0~19.0°, 9.0~17.0°, or 9.0~15.0°). Even when manufacturing films with a contact angle less than 5.0°, no significant difference in practical effect has been observed, and productivity is sometimes very low; therefore, a contact angle of 5.0° or more is preferred. This contact angle can be appropriately adjusted by changing the amount of surfactant contained in the sealing layer.

[0049] (Preferred method for thin film)

[0050] From the viewpoint of making the polyester-based sealing film of the present invention into a single material, as the film raw material in the present invention, each layer of the sealing layer and the heat-resistant layer preferably contains 50% by mass or more of polyester, more preferably 75% by mass or more. Furthermore, in each layer of the sealing layer and the heat-resistant layer, the polyester content in 100% by mass of the resin constituting each layer is preferably 50 to 100% by mass, more preferably 75 to 100% by mass, and even more preferably 85 to 100% by mass. The polyester in the present invention includes homopolymer polyester and / or copolymer polyester. Specifically, it may also include any one of the following: homopolymer polyester alone, copolymer polyester alone, blends of two or more homopolymer polyesters, blends of two or more copolymer polyesters, or blends of one or more homopolymer polyesters and one or more copolymer polyesters.

[0051] The aforementioned copolyester comprises an aromatic dicarboxylic acid component, ethylene glycol, and a copolymer component other than ethylene glycol. As the aforementioned aromatic dicarboxylic acid component, terephthalic acid, isophthalic acid, naphthalic acid, or their esterifying derivatives are preferred. The amount of terephthalic acid and / or naphthalic acid relative to the total dicarboxylic acid component is preferably 70 mol% or more, more preferably 85 mol% or more, further preferably 95 mol% or more, and particularly preferably 100 mol%. Examples of other copolymer components include diethylene glycol, neopentyl glycol, and cyclohexanediol.

[0052] Diethylene glycol is preferred as the copolymer component in the copolyester. In particular, when the sealing layer contains a copolyester, diethylene glycol is most likely to be included as the copolymer component. Using diethylene glycol (preferably only diethylene glycol) as the copolymer component in the sealing layer is suitable for imparting good heat-sealing properties, and furthermore, it also exhibits excellent transparency and heat resistance. Through moderate crystallinity, it promotes crystallization during high-temperature heat sealing, thus preventing excessive increases in sealing strength during high-temperature sealing. It can exhibit moderate sealing strength over a wide temperature range, which is also preferable. It should be noted that using only diethylene glycol as the copolymer component in the sealing layer means that the polyester constituting the sealing layer is a copolyester whose dicarboxylic acid component is only terephthalic acid and whose glycol component includes both ethylene glycol and diethylene glycol.

[0053] Furthermore, when using a copolyester composed of an aromatic dicarboxylic acid component and a diol component containing diethylene glycol and ethylene glycol as the polyester, if the diol component of the copolyester constituting the sealing layer is set to 100 mol%, the diethylene glycol component ratio is, for example, 11.0 to 19.0 mol%, preferably 12.0 to 18.0 mol%. The upper limit of the diethylene glycol component ratio of the sealing layer is more preferably 17.5 mol%, further preferably 17.0 mol%, and particularly preferably 16.5 mol%. The lower limit of the diethylene glycol component ratio of the sealing layer is more preferably 12.5 mol%, further preferably 13.0 mol%, and particularly preferably 13.5 mol% (i.e., preferably 11.0 to 19.0 mol%, 12.0 to 18.0 mol%, 12.5 to 17.5 mol%, 13.0 to 17.0 mol%, or 13.5 to 16.5 mol%). If within the aforementioned range, good heat-sealing properties can be imparted to the sealing layer.

[0054] If the amount of diethylene glycol relative to the total glycol composition is 11.0 mol% or more, it is easier to achieve a 1340 cm⁻¹ value in the FT-IR ATR measurement of the sealing layer. -1 Nearby (1330~1350cm) -1 The maximum peak intensity at () divided by 1410cm -1 Nearby (1400~1420cm) -1 The crystallinity (value) obtained by measuring the maximum peak intensity at the point is controlled to be below 0.9. In addition, the crystallization temperature of the sealing layer measured by DSC is easily controlled to be 93~118°C, and a suitable sealing strength can be easily obtained over a wide range of heat sealing temperatures, which is therefore preferred.

[0055] Furthermore, in the heat-resistant layer, when the glycol content of the polyester constituting the heat-resistant layer is set to 100 mol%, the ethylene glycol content ratio is preferably 70 to 100 mol%. The lower limit of the ethylene glycol content ratio in the heat-resistant layer is more preferably 75 mol%, further preferably 80 mol%, particularly preferably 85 mol%, and most preferably 90 mol%. By setting the ethylene glycol content ratio of the heat-resistant layer to 70 to 100 mol%, the melting point of the heat-resistant layer can be easily controlled above 200°C, which can suppress the film from adhering to the sealing rod during heat sealing, and is therefore preferred. The glycol content of the polyester constituting the heat-resistant layer can be 100 mol% ethylene glycol, but in the case of a copolyester containing other glycol components, the other glycol components besides ethylene glycol are preferably diethylene glycol. In the heat-resistant layer, when the glycol content of the polyester constituting the heat-resistant layer is set to 100 mol%, the diethylene glycol content ratio is preferably 0 to 11 mol%, more preferably 0 to 5 mol%, further preferably 0 to 3 mol%, and most preferably 0 mol%.

[0056] In this invention, alkaline earth metal compounds, manganese compounds, cobalt compounds, aluminum compounds, antimony compounds, titanium compounds, titanium / silicon composite oxides, germanium compounds, etc., can be used as catalysts for manufacturing polyester. Among these, from the viewpoint of catalytic activity, titanium compounds, antimony compounds, germanium compounds, and aluminum compounds are preferred.

[0057] In manufacturing the aforementioned polyester, it is preferable to add a phosphorus compound as a heat stabilizer. Phosphoric acid, phosphorous acid, etc., are preferred examples of such phosphorus compounds.

[0058] The intrinsic viscosity of the aforementioned polyester is preferably 0.50 dl / g or higher, more preferably 0.55 dl / g or higher, and particularly preferably 0.60 dl / g or higher. If the intrinsic viscosity is 0.50 dl / g or higher, the film-forming stability is easily improved, and therefore this is preferred. Furthermore, when a filter for removing foreign matter is provided on the melt line, from the viewpoint of discharge stability during molten resin extrusion, it is preferable that the upper limit of the intrinsic viscosity is 1.0 dl / g (i.e., preferably 0.50~1.0 dl / g, 0.55~1.0 dl / g, or 0.60~1.0 dl / g).

[0059] The thickness of the heat-resistant layer is preferably 5 μm or more. The lower limit of the heat-resistant layer thickness is more preferably 10 μm, and particularly preferably 15 μm. On the other hand, the upper limit of the heat-resistant layer thickness is preferably 50 μm, and more preferably 40 μm (i.e., preferably 5~50 μm, 10~50 μm, or 15~40 μm). If the thickness of the aforementioned heat-resistant layer is 5 μm or more, a film that is not easily broken during film formation or peeling after heat sealing can be obtained, which is therefore preferred. Furthermore, if the thickness of the aforementioned heat-resistant layer is set to 50 μm or less, stress tends to increase during film stretching, making it easier to obtain a film with excellent thickness accuracy, which is also preferred.

[0060] The sealing layer can be formed by coating or co-extrusion. Co-extrusion is a preferred method because it eliminates the need for solvents, resulting in reduced environmental impact and improved economic efficiency.

[0061] The thickness of the sealing layer is preferably 5 μm or more. The lower limit of the sealing layer thickness is more preferably 7 μm, and particularly preferably 9 μm. On the other hand, the upper limit of the sealing layer thickness is preferably 25 μm, more preferably 23 μm, and particularly preferably 21 μm (i.e., preferably 5~25 μm, 7~23 μm, or 9~21 μm). If the thickness of the sealing layer is 5 μm or more, it is easy to obtain adequate sealing strength during heat sealing, and therefore preferred. Furthermore, if the thickness of the sealing layer is 25 μm or less, it is less likely to cause cohesive failure of the sealing layer during peeling of the film after heat sealing, and sufficient heat sealing strength is easily obtained, and therefore preferred. The thickness ratio of the sealing layer to the heat-resistant layer is preferably 5:95 to 95:5, more preferably 10:90 to 60:40, and even more preferably 20:80 to 40:60. If within the aforementioned range, a film with adequate heat sealing strength and not easily broken is obtained. It should be noted that, in this disclosure, the thickness of each layer constituting the film of the present invention can be calculated from the aforementioned film thickness and the mass ratio of each layer.

[0062] The thickness of the laminated film used as the polyester-based sealing film of the present invention is preferably 10 μm or more. The lower limit of the thickness of the laminated film is more preferably 15 μm, and particularly preferably 20 μm. On the other hand, the upper limit of the thickness of the laminated film is preferably 70 μm, more preferably 65 μm, and particularly preferably 60 μm (i.e., preferably 10-70 μm, 15-65 μm, or 20-60 μm). If the thickness of the aforementioned laminated film is 10 μm or more, the film is less likely to break when peeling off the heat-sealed film, which is therefore preferable. Furthermore, if the thickness of the aforementioned laminated film is 70 μm or less, heat is easily transferred to the surface of the sealing layer during heat sealing, and a suitable heat-sealing strength is easily obtained, which is also preferable.

[0063] Furthermore, it is preferable to form irregularities on the film surface to improve the film's slip properties, rollability, and other processability. As a method for forming irregularities on the film surface, it is preferable to use a method that incorporates particles into the film. When the film contains particles, they may be contained in the sealing layer, but it is preferable that they are primarily contained in the heat-resistant layer. When the film of the present invention contains particles, the mass ratio of particles contained in the sealing layer to particles contained in the heat-resistant layer (sealing layer: heat-resistant layer) is preferably 0:100 to 100:0, more preferably 0:100 to 45:55, further preferably 0:100 to 20:80, and even more preferably 0:100 to 5:95.

[0064] As for the aforementioned particles, particles with an average particle size of 0.01 to 6 μm are preferred. Examples of such particles include tiny particles formed inside the film (internal precipitates) and particles formed outside the film, such as inorganic and / or organic particles (external particles). External particles are preferred to facilitate control over the physical properties of the particles. If particles with an average particle size of 6 μm or less are used, defects in the film are less likely to occur, and good designability and transparency are easily obtained, which is therefore preferred. Furthermore, if the average particle size of the aforementioned particles is 0.01 μm or more, good sliding properties, winding properties, and other characteristics of the film can be obtained, resulting in good processability, which is also preferred. From the viewpoint of processability such as sliding properties and winding properties, the lower limit of the average particle size of the aforementioned particles is more preferably set to 0.1 μm, and more preferably 0.5 μm. On the other hand, from the viewpoint of transparency and reducing film defects caused by coarse protrusions, the upper limit of the average particle size of the aforementioned particles is more preferably set to 5 μm, further preferably 3 μm, and even more preferably 2 μm (i.e., preferably 0.01~6 μm, 0.1~5 μm, 0.1~3 μm or 0.5~2 μm).

[0065] It should be noted that the average particle size can be calculated as follows: take multiple photos of at least 200 particles using scanning electron microscopy (SEM), trace the outline of the particles on an OHP film, and use an image analysis device to convert the traced image into the equivalent diameter of a circle.

[0066] As an example of the aforementioned internal particles, particles obtained by in-situ synthesis can be cited: metal ions are introduced into a polymer matrix, followed by chemical reduction or heating treatment, thereby causing metal nanoparticles to precipitate inside the polymer matrix.

[0067] As the aforementioned external particles, inorganic particles such as wet and dry colloidal silica, colloidal silica, aluminum silicate, titanium dioxide, calcium carbonate, calcium phosphate, barium sulfate, alumina, mica, kaolin, clay, hydroxyapatite, glass, and silica-alumina composite oxides can be used; as well as organic particles composed of styrene, organosilicon, acrylic acid (meth)acrylic acid, polyester, divinylbenzene, etc. are preferred. Among these, inorganic particles such as wet and dry colloidal silica and alumina, and organic particles composed of styrene, organosilicon, acrylic acid, methacrylic acid, polyester, divinylbenzene, etc. are preferred. These particles can be used alone or in combination of two or more without impairing the characteristics specified in this invention.

[0068] Furthermore, the content of the aforementioned particles in the polyester-based sealing film of the present invention is preferably in the range of 0.01 to 25% by mass, more preferably 0.02 to 15% by mass, even more preferably 0.03 to 10% by mass, and even more preferably 0.04 to 5% by mass. If it is set to 0.01% by mass or more, good sliding properties of the film are easily obtained, the winding property is improved, and good processability is obtained, so it is preferred. In addition, if it is set to 25% by mass or less, good transparency is easily obtained, and large protrusions are less likely to form, and good film-forming properties and transparency are easily obtained, so it is preferred.

[0069] For the heat-resistant layer constituting the polyester-based sealing film of the present invention, different types of polyester compositions can be used to form a laminated structure by known methods in order to impart other functions. The shape of this laminated film is not particularly limited. For example, when the layers formed using different extruders are designated as surface layer X, substrate layer Y, and other layers Z, examples include two 2-layer configurations of X / Y, two 3-layer configurations of X / Y / X, and three 3-layer configurations of X / Y / Z. In the case of two 2-layer configurations of X / Y, it is preferable to laminate a sealing layer on the surface of the substrate layer Y on the side where the surface layer X is not laminated (i.e., a laminated structure in the order of X / Y / sealing layer). In the case of three 3-layer configurations of X / Y / Z, it is preferable to laminate a sealing layer on the surface of the other layers Z on the side where the substrate layer Y is not laminated (i.e., a laminated structure in the order of X / Y / Z / sealing layer).

[0070] To achieve high transparency while maintaining the processability of the film, the heat-resistant layer preferably has a structure consisting of a substrate layer and a surface layer stacked together, and more preferably, a sealing layer is stacked on the surface of the aforementioned substrate layer. Preferably, the aforementioned surface layer has particles with a thickness of 0.01 to 6.0 μm per layer. The upper limit of the thickness of the aforementioned surface layer can be 5.0 μm, preferably 4.0 μm, more preferably 3.0 μm, even more preferably 2.5 μm, and particularly preferably 2.0 μm (i.e., preferably 0.01 to 6.0 μm, 0.01 to 5.0 μm, 0.01 to 4.0 μm, 0.01 to 3.0 μm, 0.01 to 2.5 μm, or 0.01 μm to 2.0 μm). In this case, the particles described in the examples above can be used.

[0071] In this invention, in order to make the haze of the film less than 10%, it is preferable that the aforementioned substrate layer does not contain particles, and the aforementioned surface layer with a thickness of 0.01 to 6.0 μm is formed, thus creating a laminated structure in which particles are contained only in the surface layer.

[0072] It should be noted that the phrase "the substrate layer is substantially free of particles" as mentioned above refers to, for example, in the case of inorganic particles, a content below the detection limit when quantifying inorganic elements using fluorescence X-ray analysis. This is because even without intentionally adding particles to the substrate layer, contaminants from foreign matter may sometimes be introduced. To obtain a film with low haze and high design flexibility, it is preferable that the substrate layer is substantially free of particles; however, particles can be added to the substrate layer as long as the content is below 30 ppm.

[0073] On the other hand, when using silica particles with an average particle size of 3.0 μm or less (preferably 1.5 μm or less) as the particles contained in the surface layer, the edge portions after film cutting and the waste film generated during paper feeding can be melted again and included in the surface layer. In this case, the particle content in the surface layer is preferably set to 1500 ppm or less, more preferably 1200 ppm, and even more preferably 1000 ppm. When using silica particles with an average particle size of 3.0 μm or less, if the particle content in the surface layer is set to 1500 ppm or less, it is easy to obtain a film with low haze and excellent designability, which is therefore preferred. By reusing the film in this way, the amount of waste film is reduced and environmental adaptability is improved.

[0074] As the particles contained in the aforementioned surface layer, the same particles as those described above can be used. Among the particles, the refractive index of silica particles, glass fillers, and silica-alumina composite oxide particles is close to that of polyester, and therefore they are particularly preferred from the viewpoint of transparency.

[0075] Furthermore, the thickness ratio of the surface layer to the substrate layer is preferably 2:98 to 98:2, more preferably 5:95 to 50:50, and even more preferably 10:90 to 40:60. If it is within the aforementioned range, it becomes a film with excellent processability and transparency.

[0076] The polyester-based sealing film of the present invention can be either uniaxially stretched or biaxially stretched, preferably a biaxially stretched film. In the present invention, solvent resistance and dimensional stability, which are drawbacks of unstretched sheets, are improved through molecular orientation based on biaxial stretching.

[0077] The manufacturing method of the aforementioned biaxially oriented polyester film is not particularly limited. For example, the following method can be exemplified: after drying the polyester resin as needed, it is fed to a known melt extruder, extruded into a sheet from a slit-shaped die, and then sealed to a casting drum by electrostatic application or other means. After cooling and solidification, an unstretched sheet (preform) is obtained, and then the unstretched sheet is biaxially stretched. It is also preferable to co-extrude, in which the polyester raw materials for forming the heat-resistant layer and the polyester raw materials for forming the sealing layer are melt-extruded from their respective extruders and then laminated. In addition, the heat-resistant layer, and further the surface layer and the substrate layer can be composed of the respective polyester raw materials co-extruded and laminated.

[0078] As a biaxial stretching method, the following approach is adopted: an unstretched sheet is stretched along both the length (MD) and width (TD) directions of the film, followed by heat treatment to obtain a biaxially stretched film with the target in-plane orientation. Among these methods, from the perspective of film quality, ideally, sequential biaxial stretching methods such as the MD / TD method (stretching along the length direction followed by stretching along the width direction) or the TD / MD method (stretching along the width direction followed by stretching along the length direction) are preferred; simultaneous biaxial stretching methods are also preferred, where stretching is performed gradually and approximately simultaneously in both the length and width directions. Furthermore, in the case of simultaneous biaxial stretching, a tenter frame driven by a linear motor can also be used. Moreover, depending on the requirements, a multi-stage stretching method can also be used, where stretching is performed in multiple stages in the same direction.

[0079] The film stretching ratio during biaxial stretching is preferably set to 2.8 to 3.7 times in the length direction, more preferably 3.0 to 3.5 times, and particularly preferably 3.1 to 3.4 times. Furthermore, it is preferably set to 3.2 to 4.2 times in the width direction, more preferably 3.4 to 4.0 times, and particularly preferably 3.5 to 3.9 times. When the stretching ratio is within the aforementioned range, good film-forming properties and thickness accuracy can be obtained, and therefore it is preferred. In addition, the stretching temperature during biaxial stretching is preferably 50 to 150°C in both the length and width directions, more preferably 80 to 130°C.

[0080] For example, the following conditions are preferred as the stretching conditions when manufacturing the polyester-based sealing film of the present invention.

[0081] In longitudinal stretching, in order to ensure that the transverse stretching, which is usually performed later, can proceed smoothly, it is preferable to set the stretching temperature to 50~150℃ and the stretching ratio to 3.0~3.5 times.

[0082] Furthermore, after biaxial stretching, the film undergoes heat treatment within a tenter frame. The heat treatment is preferably performed within a temperature range of 215–235°C. The lower limit of the heat treatment temperature is more preferably 220°C, and the upper limit is more preferably 230°C (i.e., preferably 215–235°C or 220–230°C). If the heat treatment temperature is above 215°C, the crystals of the sealing layer melt, exhibiting moderate heat-sealing properties, which is therefore preferred. Conversely, if the heat treatment temperature is below 235°C, stable film-forming properties are easily obtained, which is also preferred. The heat treatment can be either tension heat treatment or relaxation heat treatment. To reduce heat shrinkage, a relaxation heat treatment of 3–10% is preferred.

[0083] Typically, methods for reducing the heat shrinkage rate at 150°C include reducing the stretch ratio and reducing the amount of copolymer components. However, the former method sometimes worsens the unevenness of the film thickness, while the latter method increases the crystallinity of the sealing layer and deteriorates the heat-sealing performance, thus making them less preferred. In this invention, to reduce the heat shrinkage rate of the polyester sealing film at 150°C, heat setting (the heat treatment described above) is preferred.

[0084] Furthermore, this application includes packaging materials and lids, which contain the polyester-based sealing film of the present invention. When using the film of the present invention as a lid, a surfactant can be added to the film to prevent water droplets from adhering to the film due to water vapor inside the container, thus preventing fogging. In this case, if the film contains a surfactant, the surfactant can be contained in either the sealing layer or the heat-resistant layer. However, if the surfactant is not added to the heat-resistant layer but only to the sealing layer, both the fogging suppression effect and the transparency of the film can be achieved, which is therefore preferred. When the film of the present invention contains a surfactant, the ratio of the concentration of the surfactant contained in the heat-resistant layer to the concentration of the surfactant contained in the sealing layer (heat-resistant layer: sealing layer) is preferably 0:100 to 100:0, more preferably 0:100 to 45:55, further preferably 0:100 to 20:80, and even more preferably 0:100 to 5:95.

[0085] Furthermore, the added surfactant is preferably set to 0.9% by mass or less of the total weight of the polyester sealing film. The upper limit of the surfactant weight relative to the total film weight is more preferably 0.8% by mass, and particularly preferably 0.7% by mass. By keeping the surfactant weight relative to the total film weight at 0.9% by mass or less, it is easy to control the haze to 10% or less, which is therefore preferred. The lower limit is not particularly limited and can be 0.05% by mass, 0.1% by mass, or 0.2% by mass (i.e., preferably 0.05 to 0.9% by mass, 0.1 to 0.8% by mass, or 0.2 to 0.7% by mass).

[0086] When used as a cover material, the polyester-based sealing film of the present invention can be surface-treated to prevent water droplets from adhering to the film and causing fogging due to water vapor inside the container. In the present invention, surface treatment of the sealing layer is preferred. Examples of surface treatment methods include corona discharge treatment, plasma treatment, etc., and there are no particular limitations. Corona discharge treatment and plasma treatment, which can be performed continuously and can be easily implemented before the winding process in the manufacturing process of the film, are preferred.

[0087] This application claims priority based on Japanese Patent Application No. 2024-035906, filed March 8, 2024. The entire contents of the description of Japanese Patent Application No. 2024-035906, filed March 8, 2024, are incorporated herein by reference.

[0088] Example

[0089] The present invention will now be described in detail through examples. It should be noted that the properties of the films obtained in each example were measured and evaluated using the following methods.

[0090] (1) Intrinsic viscosity

[0091] Accurately weigh 0.1 g of the sample and dissolve it in 25 ml of a phenol / tetrachloroethane mixture (60 / 40 by mass). Measure the viscosity using an Ostwald viscometer at 30°C. It should be noted that three measurements were performed, and the average value was calculated.

[0092] (2) Haze

[0093] The haze of the film was measured using a haze meter (manufactured by Nippon Denshoku Kogyo Co., Ltd., model 300A) in accordance with JIS K7136:2000. It should be noted that two measurements were performed, and the average value was calculated.

[0094] (3) Film thickness

[0095] Using the original Seiko EM Co., Ltd. Milltron 1202D, 5 points were measured on each of the 3 sheets, for a total of 15 points, and the average value was calculated.

[0096] (4) Thermal shrinkage rate at 150℃

[0097] For the length and width directions of the film, strip-shaped samples with a length of 150 mm and a width of 20 mm were cut, respectively. Two marks were marked at 100 mm intervals along the length direction of each sample, and the interval A between the two marks was measured under no load. Next, one side of each strip-shaped sample was suspended in a basket with a clamp under no load and placed in a Gill aging chamber at 150°C, while measuring the time. After 30 minutes, the basket was removed from the Gill aging chamber and left at room temperature for 30 minutes. Then, for each sample, the interval B was read under no load. Based on the read intervals A and B, the thermal shrinkage rate of each sample at 150°C was calculated according to the following formula.

[0098] Heat shrinkage rate (%) = {(AB) / A} × 100

[0099] (5) Crystallization temperature (Tc) and melting point (Tm) of raw materials (objects)

[0100] Using a differential scanning calorimeter (Shimadzu Corporation, FC60A), the sealing layer surface of each embodiment was removed with a razor blade, and approximately 5 mg was placed in a sample dish. The dish was then covered, and the temperature was increased from room temperature to 300°C at a rate of 10°C / min under a nitrogen atmosphere. The crystallization temperature and melting point were determined using the peak temperatures defined in JIS K7121:1987, 9.1.

[0101] (6) Heat sealing strength

[0102] Heat seal strength was determined according to JIS Z1707:2019. Specific procedures are shown. Using a heat sealer “TYB-300” (Western Machinery), the sealing layer of the film sample was bonded to the A-PET sheet obtained below. The heat seal conditions were: upper rod temperature set to 130°C, 150°C, and 180°C; pressure set to 0.2 MPa; and time set to 1 second. The bonded and heat-sealed sample was cut with a seal width of 15 mm. Peel strength was determined using a universal tensile testing machine “DSS-100” (Shimadzu Corporation) at a tensile speed of 200 mm / min. Peel strength is expressed as strength per 15 mm (N / 15 mm).

[0103] (Evaluation of film preparation using A-PET sheets)

[0104] A small sheet (A) of polyethylene terephthalate (PET) with an intrinsic viscosity of 0.62 dl / g, consisting of 100 mol% terephthalic acid units as aromatic dicarboxylic acid and 100 mol% ethylene glycol units as diol, was dried. The sheet (A) was melt-extruded from the slit of a T-die at 280°C using an extruder, and then rapidly cooled and solidified on a cooling roller at a surface temperature of 20°C. Simultaneously, an electrostatic application method was used to press the sheet against the cooling roller, resulting in an A-PET sheet with a thickness of 200 μm.

[0105] (7) Surface crystallinity (ATR method)

[0106] For the sealing layer, total internal reflection infrared absorption (FT-IR ATR measurement) was performed under the following conditions, based on the value at 1340 cm⁻¹. -1 Absorption occurred nearby at 1410 cm -1 The intensity of absorption in the vicinity is higher than that at 1340cm. -1 / 1410cm -1 Calculate the degree of crystallinity. Here, 1340 cm⁻¹ -1 The absorption is based on the variable-angle vibration of CH2 (trans-structure) of ethylene glycol, 1410 cm⁻¹. -1 It is an absorption independent of crystal structure and orientation.

[0107] (Measuring apparatus and conditions)

[0108] FT-IR device: BRUKA OPTICS, "ALPHA"

[0109] Component: Diamond

[0110] Angle of incidence: 45°

[0111] Resolution: 4cm -1

[0112] Total number of times: 128

[0113] (8) Contact angle

[0114] Under conditions of 25°C and 50%RH, a water droplet (0.9 μL) was prepared on the sealing layer surface of a thin film using a contact angle meter (manufactured by Kyowa Interface Science Co., Ltd., fully automatic contact angle meter DM-701) and its contact angle was measured. The contact angle is the contact angle 30 seconds after being dropped onto the thin film, and the average value of 5 measurements was used.

[0115] (9) Anti-fog properties

[0116] 1) Put 300cc of warm water at 53℃ into a 500cc top-opening container.

[0117] 2) Use the sealing layer of the film as the inside to seal the opening of the container.

[0118] 3) Place at 5℃ for 30 minutes.

[0119] 4) Evaluate the condensation adhesion on the film surface.

[0120] Areas with condensation covering up to 1 / 10 of the surface area are rated as ○, while areas with condensation covering more than 1 / 10 of the surface area are rated as △.

[0121] Example 1

[0122] Small pieces of copolyester (B) with an intrinsic viscosity of 0.68 dl / g, comprising 100 mol% terephthalic acid units (an aromatic dicarboxylic acid component), 78 mol% ethylene glycol units (a diol component), and 22 mol% diethylene glycol units (a diol component), comprising polyethylene terephthalate (A) with an intrinsic viscosity of 0.62 dl / g, and polyethylene terephthalate (C) with an intrinsic viscosity of 0.62 dl / g and containing 0.72 wt% amorphous silica with an average particle size (SEM method) of 2.7 μm, were dried separately. Then, small pieces (A) and (C) were mixed in a mass ratio of 87.5:12.5 (mixed material 1). Additionally, small pieces (B) and (A) were mixed in a mass ratio of 81.8:18.2 (mixed material 2). Next, using an extruder, the small piece (A) is melt-extruded from the slit of the T die at 280°C as a substrate layer (substrate layer Y) of 57% by mass, mixed raw material 1 as a surface layer (surface layer X) of 8% by mass located on one side of the substrate layer, and mixed raw material 2 as a sealing layer (sealing layer Z) of 35% by mass located on one side of the substrate layer that is different from the aforementioned surface layer. The sheet is then rapidly cooled and solidified on a cooling roller with a surface temperature of 20°C, while simultaneously being sealed to the cooling roller using an electrostatic application method, thus obtaining an amorphous unstretched sheet.

[0123] The obtained unstretched sheet was stretched longitudinally at 115°C to 3.5 times its original thickness between heating and cooling rollers. Next, the uniaxially stretched film was fed into a tenter frame, heated at 105°C for 16 seconds, and then transversely stretched to 4.0 times its original thickness at 120°C. Subsequently, it underwent heat treatment at 230°C, followed by a 5% relaxation treatment in the transverse direction. Then, corona discharge treatment was performed on the surface of the sealing layer using a corona discharge treatment machine manufactured by Kasuga Electric Co., Ltd., with an output power of 0.3 kW, to obtain a biaxially stretched polyester film with a thickness of 30 μm.

[0124] Example 2

[0125] In Example 1, the heat setting temperature was set to 215°C, and otherwise, a biaxially stretched polyester film was obtained in the same manner as in Example 1.

[0126] Comparative Example 1

[0127] In Example 1, the heat setting temperature was set to 240°C, and otherwise, a biaxially stretched polyester film was obtained in the same manner as in Example 1.

[0128] Comparative Example 2

[0129] In Example 1, the heat setting temperature was set to 210°C, and otherwise, a biaxially stretched polyester film was obtained in the same manner as in Example 1.

[0130] Example 3

[0131] In Example 1, the raw materials for sealing layer Z were mixed such that piece (B) and piece (A) were in a mass ratio of 54.5:45.5, otherwise, a biaxially stretched polyester film was obtained in the same manner as in Example 1.

[0132] Comparative Example 3

[0133] In Example 1, the raw material for the sealing layer Z was only a small piece (B), and otherwise, a biaxially stretched polyester film was obtained in the same manner as in Example 1.

[0134] Comparative Example 4

[0135] In Example 1, the raw materials for the sealing layer Z were mixed such that the small pieces (B) and (A) were in a mass ratio of 45.5:54.5, otherwise, a biaxially stretched polyester film was obtained in the same manner as in Example 1.

[0136] Example 4

[0137] In Example 1, the thickness was set to 20 μm, and otherwise, a biaxially stretched polyester film was obtained in the same manner as in Example 1.

[0138] Example 5

[0139] In Example 1, the thickness was set to 50 μm, and otherwise, a biaxially stretched polyester film was obtained in the same manner as in Example 1.

[0140] Example 6

[0141] In Example 1, the thickness was set to 70 μm, and otherwise, a biaxially stretched polyester film was obtained in the same manner as in Example 1.

[0142] Comparative Example 5

[0143] In Example 1, the thickness was set to 80 μm, and otherwise, a biaxially stretched polyester film was obtained in the same manner as in Example 1.

[0144] Example 7

[0145] In Example 1, the raw materials of substrate layer Y were mixed by drying small pieces (B) and small pieces (A) separately and mixing them in a mass ratio of 81.8:18.2. Otherwise, a biaxially stretched polyester film was obtained in the same manner as in Example 1.

[0146] Example 8

[0147] In Example 1, the raw materials for sealing layer Z were mixed such that small pieces (B) and small pieces (A) were mixed with ELECUTT S-618-A1 (small piece D) from Takemoto Oils & Fats Co., Ltd., which is mainly composed of polyethylene terephthalate and contains 20% by mass of surfactant, in a mass ratio of 81.8:7.2:11.0. Otherwise, a biaxially stretched polyester film was obtained in the same manner as in Example 1.

[0148] Example 9

[0149] In Example 8, the transverse stretch ratio was set to 3.4 times, and otherwise, a biaxially stretched polyester film was obtained in the same manner as in Example 8.

[0150] Example 10

[0151] In Example 8, the longitudinal stretch ratio was set to 3.0 times, and otherwise, a biaxially stretched polyester film was obtained in the same manner as in Example 8.

[0152] Example 11

[0153] In Example 1, the raw materials for sealing layer Z were mixed such that the mass ratio of small piece (B) to small piece (A) to (small piece D) was 81.8:14.2:4.0, otherwise, a biaxially stretched polyester film was obtained in the same manner as in Example 1.

[0154] Comparative Example 6

[0155] In Example 1, the raw material for surface layer Z was mixed by drying small pieces (B) and small pieces (A) with ELECT S-618-A1 (D) from Takemoto Oils Co., Ltd., and mixing them in a mass ratio of 81.8:5.2:13.0. Otherwise, a biaxially stretched polyester film was obtained in the same manner as in Example 1.

[0156] Comparative Example 7

[0157] Copolyester flakes (E), (A), (C), and (D), comprising 100 mol% terephthalic acid (an aromatic dicarboxylic acid), 70 mol% ethylene glycol (a diol), and 30 mol% neopentyl glycol (a neopentyl glycol), with an intrinsic viscosity of 0.75 dl / g, were dried separately. Flakes (A), (C), and (E) were then mixed in a mass ratio of 52.0:8.0:40.0 (mixed material 3). Flakes (A) and (E) were then mixed in a mass ratio of 60:40 (mixed material 4). Finally, flakes (E), (A), (C), and (D) were mixed in a mass ratio of 68.0:6.0:6.0:20.0 (mixed material 5). Next, using an extruder, the mixed raw material 4 is melt-extruded at 280°C from the slit of the T-die in the form of a 44% mass base layer (base layer Y), the mixed raw material 3 is a 12% mass surface layer (surface layer X) located on one side of the base layer, and the mixed raw material 5 is a 44% mass surface layer (sealing layer Z) located on one side of the base layer that is different from the aforementioned surface layer. The mixture is then rapidly cooled and solidified on a cooling roller with a surface temperature of 20°C, while simultaneously being sealed to the cooling roller using an electrostatic application method, thus obtaining an amorphous unstretched sheet.

[0158] The obtained unstretched sheet was stretched longitudinally to 3.2 times its original thickness at 130°C between heating and cooling rollers, followed by a 15% relaxation treatment in the longitudinal direction. Next, the uniaxially stretched film was fed into a tenter frame, heated at 118°C for 8.6 seconds, and then transversely stretched to 4.0 times its original thickness at 120°C. Subsequently, it underwent heat treatment at 225°C, followed by a 3% relaxation treatment in the transverse direction. Finally, corona discharge treatment was performed on the surface of the sealing layer using a corona discharge treatment machine manufactured by Kasuga Electric Co., Ltd., with an output power of 0.3 kW, resulting in a 30 μm thick biaxially stretched polyester film.

[0159] In each embodiment, a high sealing range and high transparency were achieved.

[0160] In Comparative Example 1, the heat setting temperature was increased compared to Example 1, resulting in a crystallinity of less than 0.3 in the sealing layer and an increase in amorphous content. As a result, the heat sealing strength was increased and the ease of peeling in high-temperature sealing was reduced.

[0161] In Comparative Example 2, the heat setting temperature was low, resulting in less melting of the crystals in the sealing layer and a crystallinity greater than 0.9. Therefore, the sealing strength at 130°C and 150°C was lower.

[0162] In Comparative Example 3, compared with Example 1, the amount of diethylene glycol copolymer in the sealing layer was increased. As a result, the crystallinity of the sealing layer was less than 0.3, the amorphous component increased, and therefore the heat seal strength was higher and the easy peeling in high temperature sealing was reduced.

[0163] In Comparative Example 4, the amount of diethylene glycol copolymer in the sealing layer was reduced compared to Example 3. As a result, the crystallinity of the sealing layer was greater than 0.9, the amorphous component was reduced, and therefore the heat-sealing performance was reduced.

[0164] In Comparative Example 5, the film thickness was increased compared to Example 5. As a result, insufficient heat was transferred to the surface of the sealing layer during heat sealing, and sufficient sealing strength was not obtained during heat sealing at low temperatures.

[0165] In Comparative Example 6, compared with Example 10, the amount of surfactant added to the sealing layer was increased, resulting in increased surfactant exudation and decreased heat sealability.

[0166] In Comparative Example 7, the copolymer PET used in the sealing layer was neopentyl glycol copolymer PET with low crystallinity. As a result, the crystallization temperature of the sealing layer increased, and the crystallization of the sealing layer was insufficient during high-temperature sealing. Therefore, the sealing strength was excessively increased during high-temperature sealing, and the range of appropriate sealing strength was narrowed.

[0167] [Table 1]

[0168]

[0169] [Table 2]

[0170]

[0171] Industrial availability

[0172] Although the polyester-based sealing film of the present invention is made of a single material, it can achieve moderate heat-sealing strength over a wide temperature range.

Claims

1. A polyester-based sealing film comprising: a sealing layer exhibiting heat-sealing properties and a heat-resistant layer laminated on the sealing layer, wherein, The crystallinity of the surface of the sealing layer on the side without the heat-resistant layer, based on the ATR method, is below 0.

90. The crystallization temperature of the sealing layer, as determined by DSC, is 93~118℃. When the A-PET sheet is overlapped with the sealing layer and heat-sealed for 1 second under a load of 0.2MPa, the heat-sealing strength at heat-sealing temperatures of 130℃, 150℃, and 180℃ is 6~20N / 15mm.

2. The polyester-based sealing film according to claim 1 has a haze of 10.0% or less.

3. The polyester-based sealing film according to claim 1, wherein, The thermal shrinkage rate at 150°C in both the length and width directions is 0.01~4.0%.

4. The polyester-based sealing film according to claim 1, further comprising particles, The average particle size of the particles is 0.01~6μm. The content of the particles in the polyester sealing film is 0.01~25% by mass.

5. The polyester-based sealing film according to claim 1, wherein, The mass ratio of particles in the sealing layer to particles in the heat-resistant layer, i.e., sealing layer:heat-resistant layer, is 0:100~45:

55.

6. The polyester-based sealing film according to claim 1, wherein, The contact angle of the sealing layer surface with respect to water is less than 21.0°.

7. The polyester-based sealing film according to claim 1, wherein, The thickness of the heat-resistant layer is less than 50 μm.

8. The polyester-based sealing film according to claim 1, wherein, In the sealing layer, the content of polyester in 100% by mass of the resin constituting the sealing layer is 50-100% by mass.

9. The polyester-based sealing film according to claim 8, wherein, The polyester is a homopolymer polyester and / or a copolymer polyester.

10. The polyester-based sealing film according to claim 1, wherein, The sealing layer comprises a copolyester, and diethylene glycol is included as a copolymer component of the copolyester.

11. The polyester-based sealing film according to claim 10, wherein, When the diol content of the copolyester contained in the sealing layer is set to 100 mol%, the diethylene glycol content ratio is 11.0~19.0 mol.

12. The polyester-based sealing film according to claim 1, wherein, In the heat-resistant layer, the polyester content is 50-100% by mass of 100% by mass of the resin constituting the heat-resistant layer.

13. The polyester-based sealing film according to claim 12, wherein, The polyester is a homopolymer polyester and / or a copolymer polyester.

14. The polyester-based sealing film according to claim 12, wherein, When the glycol content of the polyester contained in the heat-resistant layer is set to 100 mol%, the ethylene glycol content ratio is 70-100 mol.

15. The polyester-based sealing film according to claim 1, further comprising a surfactant.

16. The polyester-based sealing film according to claim 15, wherein, The ratio of the concentration of the surfactant contained in the heat-resistant layer to the concentration of the surfactant contained in the sealing layer, i.e., the heat-resistant layer: sealing layer, is 0:100~45:

55.

17. A cover material comprising a polyester sealing film according to any one of claims 1 to 16.

18. A packaging material comprising a polyester-based sealing film according to any one of claims 1 to 16.

Citation Information

Patent Citations

  • Easy opening packaging material

    JP2001328221A

  • Sealant film and packaging material

    JP2019171792A

  • Control system of power-generating plant, power-generating plant, method of controlling power-generating plant, and power-generating plant control program

    JP2024035906A